Chapter Introduzione. La narrazione come incontro - CIOTTI, Fabio (Moderna/Comparata, 2022)
Narrative has been a subject of theoretical reflection and empirical investigation since Aristotle's Poetics. The past century has seen a growing interest in it, from an increasingly interdisciplinary perspective, leading to a truly "narrative turn" in the humanities and social sciences. The purpose of this volume is to provide an overview of this vast scholarly production, focusing in particular on: theories of narrative at the intersection of cognitive, evolutionary and computational approaches; narrative and cognitive neuroscience; and narrative and storytelling as socio-communicative phenomena.